CHALLENGES AND GAP CAPACITY OF PALM OIL FARMERS IN ACCESSING DIGITAL EXTENSION AND ASSISTANCE SERVICES - Purwadi, Purwadi; Firmansyah, Erick; Nurjanah, Danik (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Palm oil cultivation practices in the future must adopt good agricultural practices (GAP) to ensure sustainability and market acceptance. If farmers fail to implement GAP, they will face the threat of being marginalized and even eliminated from the supply chain. Extension services can be a means of disseminating information regarding the palm oil GAP. With the development of ICT, opportunities have opened up to use digital platforms as a medium for extension. In this research, a socio-economic and demographic characteristics of farmers for digital-based extension services was studied. Farmer data from four locations namely East Kotawaringin, Paser, Sekadau, and Central Mamuju were collected. Data from each parameter component at each location was analyzed for variance (Anova) at a 5% level of significance. The results show that the level of education is directly proportional, while age is inversely proportional to the level of ownership of smartphones as a means of digital education. The existence of farmer groups increases the percentage of conventional extension received by farmers, and where farmers also get information regarding the availability of digital extension materials. The variations in the level of importance and type of information needed by farmers are caused by the development phases of oil palm plantations. Recommendations for overcoming challenges and reducing the gap in farmer capacity in accessing digital extension is development of an integrated digital platform specifically for extension on oil palm cultivation that is adaptive to the needs of farmers and to various digital tools to enhance dissemination.